Corporate governance and voluntary disclosure of sustainability performance: the case of Jordan - Al Amosh, Hamzeh; Khatib, Saleh F. A. (SN Business & Economics, 2021)
Non-financial information is subject to development based on the expectations of stakeholders. As the financial information alone no longer satisfies their desires, this has contributed to improving the phenomenon of disclosure for many countries, especially in issues related to sustainability. In Jordan, disclosure practices are still emerging and voluntary. This study, therefore, investigates the level of environmental, social, and governance (ESG) disclosure in the published annual reports of industrial companies listed on the Amman Stock Exchange and examines several factors related to corporate governance mechanisms and their impact on the level of disclosure. The current study used content analysis to determine the level of disclosure. The results showed that the level of disclosure on ESG performance is still weak. Still, it is developing over time in response to the pressure of stakeholders. The results also revealed a significant impact of the board size and board meetings on the ESG performance. In contrast, the results were disappointing concerning the rest of the proposed factors (non-executive directors, audit committee, auditor type, and board compensation). It did not play any role in explaining the practices of companies in the disclosure of ESG. The case study results help shed light on the interaction of the Jordanian industrial companies listed on sustainability issues. They are considered of interest to various stakeholders, regulators, and relevant government agencies and provide recent evidence of disclosure literature in emerging countries.